2014
DOI: 10.9778/cmajo.20130025
|View full text |Cite
|
Sign up to set email alerts
|

Rates of breast cancer surgery in Canada from 2007/08 to 2009/10: retrospective cohort study

Abstract: There is substantial interprovincial variation in surgical care for breast cancer in Canada. Further research is needed to better understand such variation, and continued monitoring should be the focus of quality initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 39 publications
(32 reference statements)
4
37
1
Order By: Relevance
“…In 2004, the eligible age range for screening in NZ was widened to include women aged 45–49 years in addition to the 50–69 year age group, which could partly explain the slightly higher rate of BCS. We have shown fairly stable rates of mastectomy, slightly higher than the reported rate of 39% in Australia over a similar time period, higher than the UK audit data for screen‐detected cancers of 23% from 2013/2014 to 2014/2015, and within variable provincial Canadian rates of 26–69% …”
Section: Discussioncontrasting
confidence: 42%
“…In 2004, the eligible age range for screening in NZ was widened to include women aged 45–49 years in addition to the 50–69 year age group, which could partly explain the slightly higher rate of BCS. We have shown fairly stable rates of mastectomy, slightly higher than the reported rate of 39% in Australia over a similar time period, higher than the UK audit data for screen‐detected cancers of 23% from 2013/2014 to 2014/2015, and within variable provincial Canadian rates of 26–69% …”
Section: Discussioncontrasting
confidence: 42%
“…In contrast, during a similar time period in Switzerland, CPM rates remained stable at 7% [8] . In Canada, the only reported data examined national CPM rates between 2007 and 2010 and demonstrated an overall CPM rate of 6% (5% in 2007/2008 to 7% in 2009/2010) -consistent with our institutional results and the rates from Switzerland [8,10] . Interestingly, the factors associated with increased rates of immediate CPM at our institution are similar to those found in the United States literature -suggesting that the patient factors influencing the decision to undergo a CPM are possibly the same between the two countries.…”
Section: Discussionsupporting
confidence: 87%
“…It is possible that in these countries, as well as in Canada, where the health care system is based on a socialized medicine model, and surgeons routinely practice under budgetary restraints; a nonlife-saving surgical service such as CPM may not be as readily available as in the United States. In Canada, lower CPM rates have been noted on a national level compared to the United States [10] , but these rates were obtained through administrative databases and no patient level, surgical procedure detail, or outcomes data were reported [10] . Since CPM rates are known to be influenced by resource factors, such as access to genetic testing and immediate breast reconstruction, and other patient factors such as age [1][2][3]7,8,[11][12][13][14] , examining CPM trends with patient and procedure level data will provide more detailed information on the CPM landscape in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of research that has reported on CPM rates has been conducted in the United States, where CPM rates have ranged from 4% to 25%. [1][2][3][4] Lower rates of CPM have been reported in Canada (6%) 5 and Europe (3%). 6 Rates of CPM are increasing despite the fact that it does not offer a survival advantage for the majority of women with unilateral breast cancer.…”
Section: Introductionmentioning
confidence: 98%